2005
DOI: 10.1007/s11205-004-5577-x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Relationship Between Spirituality and Quality of Life

Abstract: The relationship between spirituality and various dimensions of health and quality of life has been extensively examined during the past decade. Though several literature reviews have been conducted in an attempt to synthesize research findings pertaining to the relationship between spirituality and health, a meta-analysis of studies examining spirituality in relation to quality of life has not been identified. The present study was designed to: (a) determine whether there is empirical support for a relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
2
21

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(181 citation statements)
references
References 84 publications
8
147
2
21
Order By: Relevance
“…According to (Sawatzky 2005), spirituality has a significant impact on job satisfaction. Analysis has shown that all the four aspects of spirituality i.e.…”
Section: Discussionmentioning
confidence: 99%
“…According to (Sawatzky 2005), spirituality has a significant impact on job satisfaction. Analysis has shown that all the four aspects of spirituality i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual disposition seems to be associated with mental health (Koenig, McCullough, & Larson, 2001;Sawatzky, Ratner, & Chiu, 2005) as it has been shown to be a predictor of happiness, psychological well-being and lower stress (Rowold, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is of pragmatic significance, as over the past few decades there has been a steadily growing body of research establishing a significant relationship between spirituality and various indices of wellbeing (Menezes & Moreira-Almeida, 2010). For example, spirituality is associated with lower rates of depression, suicide, and substance abuse (Ano & Vasconcelles, 2005;George, Larson, Koenig, & McCullough, 2000;Hackney & Sanders, 2003;Sawatzky, Ratner, & Chiu, 2005;Visser, Garssen, & Vingerhoets, 2010;Yonker, Schnabelrauch, & Dehaan, 2012). In addition, spirituality is associated with enhanced positive affect, lowered negative affect, positive relations with others, a sense of purpose in life, self-acceptance, and life satisfaction (Greenfield, Vaillant, & Marks, 2009).…”
Section: Spiritualitymentioning
confidence: 99%